(untitled) (AL MUNAZHZHARAH, 2025)
The background of this research is in decision no. 1362/Pdt.G/2016/PA.Kab.Kdr polygamy occurred without the permission of the first wife then a request for cancellation of polygamy was filed by the Petitioner against the polygamous marriage of Respondent I (husband) with another woman who the respondent continued his polygamous marriage without the permission of the Petitioner. The purpose of this study was to find out the cancellation of marriage due to polygamy without the permission of the first wife in the decision of the Religious Court of Kediri Regency, decision no. 1362/Pdt.G/2016/PA.Kab.Kdr from the perspective of Law No. 1 of 1974 and the perspective of Islamic law. The research method used is normative research and the data used are primary data and secondary data collected through documentation transcripts, then analyzed using descriptive analytical data analysis techniques. The results of this research and discussion indicate that the Petitioner has legal standing to file a Marriage Annulment Application as stipulated in Article 23 letter (d) of Law Number 1 of 1974 regarding the marriage of Respondent I to Respondent II which was carried out when Respondent I was still legally married without the permission of the Petitioner. However, in the view of Islam, polygamy without the wife’s permission cannot be a reason for submitting an annulment of marriage because the condition for polygamy in Islamic law is only to be fair to wives.